2010
DOI: 10.1016/j.neulet.2009.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NGF and GDNF family members and their receptors during peripheral nerve development and differentiation of Schwann cells in vitro

Abstract: Ligands of NGF and GDNF families of neurotrophic factors have important functions in the development of the vertebrate peripheral nervous system (PNS). It has been established that they also play key roles in the regeneration of PNS. Expression patterns of NGF and GDNF family members and their receptors have mostly been analyzed during regeneration, and less during development of the PNS. We describe the expression of mRNAs encoding these neurotrophic factors and their receptors during development of rat sciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Downstream molecules of cAMP signaling include Arginase 1 (ARG1), neuropeptide Y (NPY), protein kinase A (PKA), CREM (cAMP response element modulator), and IL-6 (Parlato et al, 2006;Spooren et al, 2010;Zhou et al, 2012). Lesion also upregulates trophic factors, such as BDNF, NGF, and NGF receptor (Averill et al, 2004;Delcroix et al, 2003;Meyer et al, 1992;Micera et al, 2007;Piirsoo et al, 2010;Wilhelm et al, 2012). c-Jun has been shown to contribute to regeneration, as the c-Jun null neurons fail to organize a proper regeneration program (Arthur-Farraj et al, 2012;Fontana et al, 2012;Yuan et al, 2012).…”
Section: Intrinsic Signals In Pns Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream molecules of cAMP signaling include Arginase 1 (ARG1), neuropeptide Y (NPY), protein kinase A (PKA), CREM (cAMP response element modulator), and IL-6 (Parlato et al, 2006;Spooren et al, 2010;Zhou et al, 2012). Lesion also upregulates trophic factors, such as BDNF, NGF, and NGF receptor (Averill et al, 2004;Delcroix et al, 2003;Meyer et al, 1992;Micera et al, 2007;Piirsoo et al, 2010;Wilhelm et al, 2012). c-Jun has been shown to contribute to regeneration, as the c-Jun null neurons fail to organize a proper regeneration program (Arthur-Farraj et al, 2012;Fontana et al, 2012;Yuan et al, 2012).…”
Section: Intrinsic Signals In Pns Regenerationmentioning
confidence: 99%
“…At the dedifferentiation stage, SCs downregulate genes related to myelin production and maintainance, including myelin structural proteins, P0, MBP, MAG, periaxin and cholesterol synthesizing enzymes (LeBlanc and Poduslo, 1990;Scherer et al, 1995;Stoll and Muller, 1999 (Johnson et al, 1988;Schmid and Maness, 2008;Tacke and Martini, 1990;Thornton et al, 2008;Triolo et al, 2006). Furthermore, dedifferentiated SCs upregulate trophic factors such as NGF, BDNF and GDNF, and cytokines, such as TNF-α, IL-1β, IL-6, LIF and MCP-1, to facilitate the regenerative program (Flugel et al, 2001;Nadeau et al, 2011;Piirsoo et al, 2010;Taskinen and Roytta, 2000;Wilhelm et al, 2012). Although the details of transcriptional control of the phenotype transition are still unclear, a recent study has demonstrated that c-Jun is actually the major controller of the dedifferentiation phenotype (Arthur-Farraj et al, 2012).…”
Section: Post-lesion Schwann Cell Activitymentioning
confidence: 99%
“…[27][28][29] Studies have revealed the participation of NGF in peripheral nerve regeneration. In this context, Piirsoo et al (2010) demonstrated significant enhancement of NGF mRNA expression in the sciatic nerve in cultured rat Schwann cells. 30 Sun et al (2009) also found that NGF is able to bind to laminin, an important component of the nerve extracellular matrix, to improve the repair of peripheral nerve injuries in a rat sciatic nerve crush injury model.…”
Section: Discussionmentioning
confidence: 86%
“…In this context, Piirsoo et al (2010) demonstrated significant enhancement of NGF mRNA expression in the sciatic nerve in cultured rat Schwann cells. 30 Sun et al (2009) also found that NGF is able to bind to laminin, an important component of the nerve extracellular matrix, to improve the repair of peripheral nerve injuries in a rat sciatic nerve crush injury model. 31 Regarding NT-3, Dong and Cheng (2009) showed that NT-3 promotes an important increase in the amplitude, motor nerve conduction velocity, number and thickness of axons, as well as in the diameter of nerve fibers, and the percentage of nerve tissue within a sciatic nerve transection in a rat nerve injury model.…”
Section: Discussionmentioning
confidence: 86%
“…18 Abnormal expression of NGF in neuronal cells and nonneuronal cells has been shown to affect peripheral nerve development. 34 …”
Section: Discussionmentioning
confidence: 99%